Effectiveness of malaria free zone program on the knowledge, attitude and practice of malaria prevention among university students in conakry, guinea: protocol of a randomized controlled trial - Sano, Aicha; Sivaratnam, Dhashani; Ahmad, Norliza; Camara, Alioune; Lim, Poh Ying (Universiti Putra Malaysia, 2023)
Introduction: Malaria is a vector-borne disease caused by the bites of infected female mosquitoes that transmit the parasite to humans. In Guinea, the entire population is at risk of malaria infection. The objective of this study is to develop, implement and evaluate the effectiveness of the Malaria Free Zone program using the Health Belief Model (HBM) to improve malaria prevention knowledge, attitudes, and practices among university students in Conakry, Guinea. Methods: The study design is a clustered randomized controlled trial (RCT). Students are selected using the clustered sampling method, with each university representing one group, either the intervention or control group. The sample size is 113 university students from each group. The content of the Malaria Free Zone program includes eight sessions, which are based on the HBM constructs. This program takes approximately 6 hours and 30 minutes to complete. Respondents are required to complete a questionnaire over four time points. Generalized Estimating Equation (GEE) will be used to determine the effectiveness of the Malaria Free Zone program on malaria prevention knowledge, attitudes, and practices, adjusted with covariates. Conclusion: It is expected that there will be a significant difference in knowledge, attitude, and practice of malaria prevention in the post-test, 2-week and 2-month follow up of the intervention group after the Malaria Free Zone program. Students in the intervention group will have significant higher knowledge, attitude and practice of malaria prevention compared to students in the control group.